Colo-rectal Cancer Risk After Cholecystectomy in Al-Khadymia Teaching Hospital (Iraqi Journal of Medical Sciences, 2016)
Background: Cholecystectomy is one of the most commonly performed operative procedures, on the other hand, the wide acceptance of laparoscopic cholecystectomy for sure led to the increased rate of cholecystectomies. The data assessing relationship between cholecystectomy and colo-rectal carcinoma is limited; therefore the relationship of whether prior cholecystectomy modifies the natural history of colo-rectal carcinoma is worth assessing in Al-Khdymia Teaching Hospital.Objective:To estimate the risk of colo-rectal carcinoma in cholecystectomized patients and to assess the feasibility of screening in these patients.Methods: Retrospective evaluation of a total of 123 patients with approved colo-rectal carcinoma over a period of eleven years in a wide district drainage referral Hospital (Al-Kadhimiya Teaching Hospital) in Baghdad-Iraq.Result:The total number of patients included is 123 from June 1999 to June 2010. The whole group approved to have a colo-rectal carcinoma. The age range is from 17-90 years, the females constitute 55 patients of the total and the rest 68 patients were males. The results were not significant regarding the gender of cholecystectomized patients and the risk of colo-rectal carcinoma. While on the other hand there were slightly increased statistically significant relative risk of colo-rectal carcinoma specially involving the proximal colon in cholecystectomized patients.Conclusions:There is an increased risk of incidence of colo-rectal carcinoma in cholecystectomized patients regardless the gender of the patient, and the risk is higher for the proximal colon than the distal colon. Key word: cholelithiasis, cholecystectomy, colo-rectal carcinoma, screening of cholecystectomized patients